Linezolid Toxicity and Mitochondrial Susceptibility: A Novel Neurological Complication in a Lebanese Patient - Abou Hassan, Ossama K.; Karnib, Mohamad; El-Khoury, Riyad; Nemer, Georges; Ahdab-Barmada, Mamdouha; BouKhalil, Pierre (Frontiers in Pharmacology, 2016)
The recent rise in the use of linezolid to treat a variety of resistant pathogens has uncovered many side effects. Some patients develop lactic acidosis, myelosuppression, optic or peripheral neuropathies and myopathies. We evaluated an elderly patient who presented to the Emergency Room with linezolid toxicity and a novel neurologic complication characterized by bilateral globi pallidi necrosis. Mitochondrial ribosome inhibition was described to be the predisposing factor. The patient belongs to the mitochondrial J1 haplotype known to be associated with side effects of the drug. We recommend based on the molecular profile of the illness pretreatment considerations and complication management.